(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Northern regions distribution of wheat field collembola in the soil was studied. Also, the spring season dynamics of the amount of collembola in the 0-30 cm soil layers in the wheat agrocenosis was observed. When the amount of collembola was studied by layers, their most common soil layer was determined to be maximum in the middle (10-20 cm) layer of the soil. In the spring season, i.e. in March, April and May, agrocenoses are averaged per 1 m2 in soil layers880 specimens were found.